Using Cu2+ ions as a detection material to verify the synthesis mechanism of Au nanoclusters mediated by wool keratin and silk fibroin resilience network. Issue 13 (July 2022) - Zhang, Xin; Dong, Yuanyuan; Liu, Gangzhong; Zhang, Guosheng; Li, Jie; Zhu, Ying; Yu, Weidong; Liu, Hongling
Nanoclusters, with their ultrasmall sizes, have emerged as an indispensable tool in designing structural materials with a wide range of applications, but predicting the synthesis mechanism and structures remains challenging. This work delineates a synthesis mechanism of gold nanoclusters (AuNCs), which is realized by functionalizing a wool keratin (WK) and silk fibroin (SF) resilience network structure via self-assembly with controllable microstructure transformation. We synthesized such AuNCs by reducing the thiol groups of WK into WK@AuNCs and then entering the WF&SF resilience framework during the reconstruction, achieving WK@AuNCs/WK&SF with high fluorescence intensity for selective quenching of heavy metal Cu 2+ ions. Further investigation indicated that α-helix and β- crystallites resulted in a soft–hard molecular segment denoted as WK&SF resilience network, which held and separated the WK@AuNCs into the nanocages. Owing to the synergism of these features, WK@AuNCs/WK&SF displayed superior fluorescence performances compared with WK@AuNCs.